잔대 추출물의 항염 및 항천식 효과 - 장환희(Hwan Hee Jang); 김미주(Mi Ju Kim); 조수연(Su Yeon Cho); 김정봉(Jung Bong Kim); 이성현(Sung Hyeon Lee); 이영민(Young Min Lee) (東아시아食生活學會誌, 2015)
Asthma is an increasing global health problem, and novel strategies to prevent or ameliorate the condition are needed. The purpose of the present study was to evaluate the anti-inflammatory and anti-asthma effects of Adenophora triphylla var. japonica extracts. We investigated the molecular mechanism underlying the effects of 80% ethanol extracts (AE) of A. triphylla on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. AE treatment inhibited pro-inflammatory cytokines such as TNF-${α}$ and IL-6 as well as nitric oxide (NO) production in LPS-stimulated RAW 264.7 cells. In particular, NO and pro-inflammatory cytokine production was suppressed more effectively by aerial parts (AE-A) than roots (AE-R) of A. triphylla. Quantitative RT-PCR assay showed that AE reduced mRNA levels of iNOS and COX-2. We also evaluated the anti-asthmatic effects of AE-A in an ovalbumin (OVA)-induced BALB/c mouse model. AE-A supplementation significantly reduced the amounts of airway eosinophils, IL-4 and IL-13 levels in BALF, and IgE levels in serum as compared with untreated, OVA-induced mice. These results suggest that AE-A can be considered as a therapeutic agent to potentially relieve asthma.